The Enforcement of Human Rights Through Implementing of The Sharia - Nurul Hakim (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2020)
Many Western law experts state that Islamic sanctions on criminal law are sadistic, cruel, so that universal human rights are violated. In the perspective of Western human rights the paradigm of thinking like that has long been embedded to this day. On the other hand, in a different perspective human rights in Islam explain that the legal sanctions contained in Islamic criminal law pay more attention to aspects of human rights, such as the protection of the rights of victims and victims' families and protect the rights of the community. The existence of death sanction in a murder case, is part of an effort to eliminate the sense of revenge, anger, that is in the victim's family. Legal sanctions in Islamic criminal law aim to provide social protection by ensuring the realization of human rights in society.